Apoptosis and remodeling in adriamycin-induced cardiomyopathy rat model - Young Mi Hong; Hyeryon Lee; Min-Sun Cho; Kwan Chang Kim (Korean Pediatric Society, 2017)
PurposeThe mechanism for the pathogenesis of adriamycin (ADR)-induced cardiomyopathy is not yet known. Different hypotheses include the production of free radicals, an interaction between ADR and nuclear components, and a disruption in cardiac-specific gene expression. Apoptosis has also been proposed as being involved in cardiac dysfunction. The purpose of this study was to determine if apoptosis might play a role in ADR-induced cardiomyopathy.MethodsMale Sprague-Dawley rats were separated into 2 groups: the control group (C group) and the experimental group (ADR 5 mg/wk for 3 weeks through intraperitoneal injections; A group). Echocardiographic images were obtained at week 3. Changes in caspase-3, B-cell leukemia/lymphoma (Bcl)-2, Bcl-2-associated X (Bax), interleukin (IL)-6, tumor necrosis factor-α, brain natriuretic peptide (BNP), troponin I, collagen 1, and collagen 3 protein expression from the left ventricle tissues of C and A group rats were determined by Western blot.ResultsAscites and heart failure as well as left ventricular hypertrophy were noted in the A group. Ejection fraction and shortening fraction were significantly lower in the A group by echocardiography. The expression of caspase-3, Bax, IL-6, BNP, collagen 1, and collagen 3 were significantly higher in the A group as compared with the C group. Protein expression of Bcl-2 decreased significantly in the A group compared with the C group.ConclusionADR induced an upregulation of caspase-3, Bax, IL-6, and collagen, as well as a depression in Bcl-2. Thus, apoptosis and fibrosis may play an important role in ADR-induced cardiomyopathy.